COLLABORATIVE GOVERNANCE DALAM IMPLEMENTASI PROGRAM KAMPUNG IKLIM DI KELURAHAN TALANGBUBUK, KECAMATAN PLAJU, KOTA PALEMBANG - Muhammad Reza Hudaya; Titis Puspita Dewi (KOMUNITAS, 2021)
Climate change that occurs globally is a strategic issue for Indonesia. One form of attention from Ministry of Environment and Forestry is implementing the Climate Village Program (ProKlim). This program can be implemented through the participation of the community at least at the level of Rukun Warga or a village that has a role in reducing the risk of climate change impacts. ProKlim has implemented a collaborative cooperation process between government and non-government actors. In general, the research objective is to describe the implementation of collaborative governance in the implementation of ProKlim in Talangbubuk Village . This research uses descriptive qualitative methods through document study and interviews, then processed from the data reduction stage, the interpretation of the findings, and data triangulation. Based on the findings analyzed using 6 (six) Collaborative Governance criteria, it can be concluded that the collaboration in ProKlim implementation can be categorized as a process collaboration.